2022
DOI: 10.3390/ijms23094571
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of Mitochondrial Dynamics—From Cardiomyocytes to Osteoblasts: A Critical Review

Abstract: Mitochondria play a crucial role in cell physiology and pathophysiology. In this context, mitochondrial dynamics and, subsequently, mitochondrial ultrastructure have increasingly become hot topics in modern research, with a focus on mitochondrial fission and fusion. Thus, the dynamics of mitochondria in several diseases have been intensively investigated, especially with a view to developing new promising treatment options. However, the majority of recent studies are performed in highly energy-dependent tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 132 publications
0
4
1
Order By: Relevance
“…PA-induced lipotoxicity has been associated with mitochondrial fission. [12,27,33,36,37]. In our studies, however, we have found that although the non-lipotoxic 25 µM PA dose induced mitochondrial fission process via activation of DRP1, this process is associated with enhanced mitochondrial respiration and mineralization.…”
Section: Discussioncontrasting
confidence: 51%
“…PA-induced lipotoxicity has been associated with mitochondrial fission. [12,27,33,36,37]. In our studies, however, we have found that although the non-lipotoxic 25 µM PA dose induced mitochondrial fission process via activation of DRP1, this process is associated with enhanced mitochondrial respiration and mineralization.…”
Section: Discussioncontrasting
confidence: 51%
“…This contradicts the findings of Sasaki and colleagues, who demonstrated that HIF-1 is upregulated in spontaneous wound healing and bone repair in a mouse model resembling osteomyelitis [ 56 ]. Since mitochondrial fission agent dynamin-related protein 1 (DRP1) is interconnected with and induced by HIF-1a [ 8 , 23 , 57 ], the inhibition of mitochondrial fission might offer a comparable target to reduce inflammation and restore bone mineralization. Because of mitochondrial fission’s central role in several cellular pathways, it offers an optimal lever to control the physiology of the cell, both for pathogens and medical agents.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the obvious direct interconnection between bone cells and infection-causing bacteria, mitochondrial dynamics and function in bone cells following infection have gained increasing attention [ 7 , 8 ]. Mitochondria are responsible not only for energy production, but also for several vital processes such as calcium homeostasis, cellular immunity and even cell death or apoptosis in eukaryotic cells [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial ultrastructure undergoes dramatic changes during metabolic perturbations or in the presence of certain genetic modifications [ 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. As such, calcium overload is a way to induce mitochondrial structural modifications.…”
Section: Structure/function Axismentioning
confidence: 99%